A Randomized Controlled Trial to Reduce Lifestyle Related Risk Factors for Non-Communicable Diseases through Funeral Societies in Sri Lanka - Dabrera, Thushani Marie Elizabeth; Pathmeswaran, Arunasalem; Kasturirathna, Anuradhani; Tillekeratne, Gayani; Østbye, Truls (Gestão e Sociedade, 2017)
A cluster randomized controlled trial was conducted to change diet, physical activity, smoking and alcohol consumption among participants through funeral societies in the Western Province. Twenty one administrative subdivisions in the Ragama area were randomized into intervention and control groups. Ten administrative subdivisions in the North Western Province were selected as an additional control group. The primary outcome was change in the proportion of individuals who consumed 5 servings or more of fruits and vegetables per day. The study showed only a modest, not significant increase in the proportion of people consuming 5 servings of fruits and vegetables or more per day. Of the secondary outcomes assessed, their intake of green leaves and mean MET minutes spent on leisure activities increased significantly more in the intervention group than in the control groups, but the differences were small. To effectively reduce non-communicable diseases (NCD) in Sri Lanka, community-based organizations could be utilized to deliver prevention programs.